Research of literature with a dominant documentary basis in Belarusian literary studies: the development of tradition - Gubskaya, Olga N. (Journal of the Belarusian State University. Philology, 2023)
The article is devoted to the problem of studying literature with a dominant documentary basis, which is relevant for modern Belarusian literary studies. The development of the Belarusian scientific tradition in the study of this issue is analysed. The work of A. M. Adamovich is defined as a starting position for studying the role of a document as a fundamental element of a literary work. It is noted that M. I. Mushinsky, L. Ya. Garanin, and D. Ya. Bugaev were among the first Belarusian scientists who were interested in the problem of factography in literature. It was they who came to the conclusion that a document within the framework of a literary work of this type should act as a conceptual core, the subject of research. L. D. Sinkova, G. K. Tychko, and A. I. Belsky represent the next generation of researchers who were attracted by the above-mentioned problem. G. K. Tychko touches on the issue of normalisation of the categorical apparatus that should be used when conducting such studies. L. D. Sinkova, as a criterion for measuring the degree of artistry or documentality, suggests the level of manifestation and the nature of accentuation of the factual basis, which leads to the following gradation of documentary fiction: fiction prose, in which fiction dominates and imitation, mystification of facts is allowed, and non-fiction prose, in which the factual basis dominates. Thus, the research attention is focused not only on the presence or absence of factographism in the work, but also on the role of the author, who consciously highlights or ignores this factographism. The article suggests further development of this concept. A literary work is perceived as an act of communication and analysed using the tools of narratology. For a group of works with an accentuated factual basis, further differentiation is proposed: the prose of the ego-document (a narrative with a dominant author’s I) and the literature of fact, or the prose of voices (a narrative with a dominant collective polyphony).
Keywords: fact; factographism; narratology; narration; form of communication; ego-document; literature of fact